1982
DOI: 10.1007/bf00265384
|View full text |Cite
|
Sign up to set email alerts
|

O,p′-DDD (Mitotane) levels in plasma and tissues during chemotherapy and at autopsy

Abstract: The distribution of o,p'-DDD in various body compartments of patients being treated for metastatic adrenocortical carcinoma was studied. A highly significant semilogarithmic relationship was found between plasma and adipose tissue concentrations during therapy and between plasma and brain at autopsy. A linear relationship was found at autopsy between concentrations in adipose tissue and those in various other tissues, such as tumour and brain. The semilogarithmic relationship can be explained by the assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 8 publications
1
24
1
1
Order By: Relevance
“…The model estimated the volume of distribution to be relatively high (161G68 l/kg LBM) and clearance to be relatively low (1.12G0.41 l/h). Moreover, previous observations of fatty tissue concentrations that were w200-fold higher than plasma concentrations are in accordance with this hypothesis (19). Since the time from baseline to peak variability in both groups seems to be comparable (3-5 h), the influence of food intake should be considered.…”
Section: European Journal Of Endocrinologysupporting
confidence: 80%
“…The model estimated the volume of distribution to be relatively high (161G68 l/kg LBM) and clearance to be relatively low (1.12G0.41 l/h). Moreover, previous observations of fatty tissue concentrations that were w200-fold higher than plasma concentrations are in accordance with this hypothesis (19). Since the time from baseline to peak variability in both groups seems to be comparable (3-5 h), the influence of food intake should be considered.…”
Section: European Journal Of Endocrinologysupporting
confidence: 80%
“…Although to our knowledge early studies did not report drug levels, two retrospective studies concluded that mitotane levels Ͼ 10 g/mL or 14 g/mL were associated with a higher response rate. 10,27,28 In the current study, no association was observed between mitotane levels Ͼ 10 g/mL or 14 g/mL and response, suggesting that mitotane levels did not have a significant effect on the efficacy of this treatment regimen.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study highlights that monitoring of plasma mitotane concentrations is of particular interest in controlling hypercortisolism. The narrow therapeutic range of mitotane is well known, and a target plasma concentration between 14 and 20 mg/l is recommended in adrenocortical cancer (31,32,33). However, the target concentration for the anti-cortisolic effect is not well established.…”
Section: Discussionmentioning
confidence: 99%